2022
DOI: 10.1186/s12905-022-01720-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the severity of perimenstrual symptoms and a regular exercise habit in Japanese young women: a cross-sectional online survey

Abstract: Background Experiencing perimenstrual symptoms is a major health concern for young women. Women in the reproductive age experience menstruation about once a month, and many experience perimenstrual symptoms. Drug therapies such as painkillers (commonly used) and hormonal medications help to achieve symptomatic relief from perimenstrual symptoms. However, many women are concerned about tolerance and compliance of the drugs used to treat perimenstrual symptoms and lack awareness on how to cope wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…These ndings support our results that the age of 15-17 years old female students with more PE class times per week had lower incidence of PMS than those without. Moreover, previous studies revealed that exercise habits of more than 30 minutes twice a week may reduce the severity of premenstrual symptoms in the women aged 18-25years 29 . The results indicated that physical exercises could be effective in reducing the incidence and severity of PMS in women aged 15-25.…”
Section: Discussionmentioning
confidence: 98%
“…These ndings support our results that the age of 15-17 years old female students with more PE class times per week had lower incidence of PMS than those without. Moreover, previous studies revealed that exercise habits of more than 30 minutes twice a week may reduce the severity of premenstrual symptoms in the women aged 18-25years 29 . The results indicated that physical exercises could be effective in reducing the incidence and severity of PMS in women aged 15-25.…”
Section: Discussionmentioning
confidence: 98%
“…However, a comparison can be made with the general population. We saw incidences of menstrual irregularities in women of childbearing age (in the absence of organic gynecological pathology, for which an unknown or dysfunctional problem is attributable), in which menstrual irregularities occur in an estimated 14% to 25% of women of childbearing age [ 38 ]. We had to deal with a large number of patients with fibroids and climacteric, which are among the main conditions of access to the clinic for menstrual irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences in the percentage of respondents who undertook coping strategies related to stretching and physical activity across severity levels. A previous study indicated the possibility that regular habitual exercise was a useful coping strategy for dysmenorrhea [51]. Considering that the more severe the dysmenorrhea, the more intense the sensory as well as affective pain, exercise could be beneficial in reducing monthly menstrual pain and associated negative emotions [51,52], thereby improving QOL.…”
Section: Plos Onementioning
confidence: 99%
“…A previous study indicated the possibility that regular habitual exercise was a useful coping strategy for dysmenorrhea [51]. Considering that the more severe the dysmenorrhea, the more intense the sensory as well as affective pain, exercise could be beneficial in reducing monthly menstrual pain and associated negative emotions [51,52], thereby improving QOL.…”
Section: Plos Onementioning
confidence: 99%